Renal Lesions in Autoimmune Pancreatitis: Diffusion Weighted Magnetic Resonance Imaging for Assessing Response to Corticosteroid Therapy - Zaheer, Atif; Halappa, Vivek Gowdra; Akshintala, Venkata S; Singh, Vikesh K; Kamel, Ihab R (JOP. Journal of the Pancreas, 2013)
Context Autoimmune pancreatitis is a rare disorder characterized by the systemic deposition of IgG4 plasma cells. Extrapancreatic manifestations of autoimmune pancreatitis depend on the site of plasma cell deposition. The most common extrapancreatic site of involvement is the bile duct followed by the retroperitoneum and kidneys. Case report We report a case of a patient with autoimmune pancreatitis and renal lesions who underwent MRI prior to and after corticosteroid therapy. Conclusion We emphasize the role of diffusion weighted imaging (DWI) and apparent diffusion coefficient (ADC) findings on MRI in evaluating the response to steroid therapy. Image: Axial post contrast T1WI through the level of the kidneys.